2004
DOI: 10.1128/iai.72.10.5662-5667.2004
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6-Dependent Mitogen-Activated Protein Kinase Activation Differentially Regulates the Production of Interleukin-12 by Macrophages in Response toToxoplasma gondii

Abstract: The production of interleukin-12 (IL-12) is critical to the development of innate and adaptive immune responses required for the control of intracellular pathogens. Many microbial products signal through Toll-like receptors (TLR) and activate NF-κB family members that are required for the production of IL-12. Recent studies suggest that components of the TLR pathway are required for the production of IL-12 in response to the parasite Toxoplasma gondii; however, the production of IL-12 in response to this paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 53 publications
3
46
0
1
Order By: Relevance
“…These findings as well as the demonstration that TRAF6 regulates maturation of dendritic cells and IL-12 production by these cells (34,35,73) suggest that this adapter protein plays an important role in resistance against intracellular pathogens.…”
Section: Discussionmentioning
confidence: 81%
“…These findings as well as the demonstration that TRAF6 regulates maturation of dendritic cells and IL-12 production by these cells (34,35,73) suggest that this adapter protein plays an important role in resistance against intracellular pathogens.…”
Section: Discussionmentioning
confidence: 81%
“…For infection with RH tachyzoites, representative of virulent type I parasite strains, IL-12 production did not require TLR/IL-1R adaptor MyD88. Activation of p38 MAPK, necessary for parasite-induced IL-12 (34,35), was also normal in MyD88 Ϫ/Ϫ macrophages infected with RH tachyzoites. p38 MAPK phosphorylation occurred in the absence of detectable MKK3, MKK4, and MKK6 activation in MKK3…”
Section: Discussionmentioning
confidence: 88%
“…We and others recently found a requirement for p38 MAPK signaling in macrophage IL-12 induction in response to soluble tachyzoite extracts and live parasites of the virulent type I RH strain (34,35). p38 MAPK activation in response to T. gondii involves parasite-induced autophosphorylation rather than a more conventional pathway of phosphorylation mediated by upstream MAPK kinases (MKK) 3 such as MKK3, MKK4, or MKK6 (34).…”
mentioning
confidence: 99%
“…For example, the parasite inhibits transcription factors associated with host defense such as NF-B (Butcher et al, 2001;Shapira et al, 2002) and STAT1␣ (Luder et al, 2001), while promoting activation of STAT3, which suppresses synthesis of IL-12 . Nevertheless, live parasites and parasite-derived products induce pro-inflammatory signaling in macrophages, including activation of the IKK complex (Shapira et al, 2005), as well as phosphorylation of the mitogen-activated protein kinases (MAPK) p38 and ERK1/2, which have been shown in several studies to be important regulators of the macrophage IL-12 response Mason et al, 2004). Previous work has demonstrated that induction of IL-12 synthesis by T. gondii requires the Toll-like receptor (TLR) adaptor molecules MyD88 (Scanga et al, 2002) and TRAF6 (Mason et al, 2004), and there is evidence that parasite recognition is mediated by one or more TLRs (Hitziger et al, 2005;Mun et al, 2003;Scanga et al, 2002;Yarovinsky et al, 2005).…”
Section: Introductionmentioning
confidence: 99%